A five years review of complications of implantable venous access devices (IVAD) in cancer patient through the cephalic vein cut down approach - Nor, Sobri (2018)
Introduction: Implanted venous access device (IVAD) is one of the options that give access to the central venous circulation. It is widely used nowadays and can be used for various reasons. It can be retained in the body for a period of up to two years with minimal care and low risk of infection thus it is suitable for patients especially for those who had the difficult vascular access example in cancer patients. Cephalic vein cut down approach is one of the methods of insertion of IVAD with minimal complication associated to this technique, however, it is not widely used as it needs to be done in operating theatre setting and it took longer duration. This study was done to evaluate the complication of the IVAD that implanted in cancer patient through cephalic vein cut down approach. Methodology: This is a retrospective study involving cancer patients that were implanted with IVAD through cephalic vein cut-down approach in HUSM from January 2010 to December 2014. All medical records reviewed and evaluated for demographics, surgical procedure, and types of IVAD, complications post implantation and possible associated factors with the complications studied. All the information collected and analyzed with SPSS programme 22.0. Results: There were 197 patients included in this study which involved 54.3% male patients and 45.7% female patients. The procedure performed by orthopaedic surgeons in 132(67%) patients, 65 patients (33%) performed by the medical officers. All patients received intravenous antibiotic prophylaxis, Cefuroxime prior to implantation. The mean duration of surgery was 59.37 minutes while the mean duration of follow up, was 715 days. The overall complication rate was 12.7% (n= 25). There were 7.6% (n=15) infection rate, 3.6% (n=7) thrombosis, 1.0% (n= 2) for fracture and migration and 0.5% (n=1) mal-position of IVAD. There was no association between the types of catheter with the overall complication rate. There was an association between the types of cancer with the infections rate. We found no association between age and absolute neutrophil count (ANC) with the infection rates and the platelet levels with thrombosis rates. Conclusions: Cephalic vein cut down approach is a safe approach for IVAD implantation with an overall low rate of complications. These treatments offer an alternative and provide benefits to patients in HUSM.